Numerical Simulation of Squeeze-Casting SiC3D/Al Ceramic Matrix Composites - Yangwei Wang; Fangzhou Zhang; Sijia Feng; Jiawei Bao; Yanni Gong; Chunyuan Yuan; Denghui Zhao (Metals, 2024)
In this study, the filling and solidification processes of squeeze-casting SiC3D/Al composites were analyzed by the ProCAST simulation software (ver. 2018.0). A practical squeeze-casting experiment was conducted to verify the accuracy of the simulation results. A series of orthogonal experiments were conducted on the initial preheating temperature of various components to identify the optimal parameters in order to achieve better porosity and stress concentration values. According to the results and analyses, the preheating temperature of the mold was the most important determining factor. Under a pouring temperature of 700 °C, mold preheating temperature of 200 °C, and SiC skeleton preheating temperature of 600 °C, the maximum principal stress at the bottom of the products was decreased by about 41.9%, and the shrinkage volume inside the composite was decreased about by about 61.6%. Thus, by adjusting the initial preheating temperature of various components, the squeeze-casting SiC3D/Al composites could achieve better performance and fewer internal defects.